Resolving challenges in tailings closure in semi-arid deserts — a case study into the decommissioning and rehabilitation of the Tanami Mine Three Cell tailings storage facility - Pang, K.L.; Lacy, H.W.B.; Haymont, R.; Potts, R. (Mine Closure 2009: Proceedings of the Fourth International Conference on Mine Closure, 2009)
Tanami Mine, located within the Tanami Desert of the Northern Territory, approximately 670 km northwest of Alice Springs, is one of the most remote mine sites in Australia. The site comprises 45 open pits, eight backfilled pits, 11 in-pit tailing storage facilities (TSF), 24 waste rock landforms, two above ground TSF, a processing plant and on-site village accommodation scattered over 70 km in length. The mine site, including TSF, has been subject to a systematic closure process over the last five years. The large Three Cell above ground paddock style TSF was seen by previous mine closure planners as a major challenge to rehabilitate, and accordingly had attracted the largest portion of the closure budget. Deposition of tailings into the TSF occurred between 1992 and 2001, and from this time the cells were allowed to dry and consolidate. The decommissioning process for the facility began in 2004, and a staged and logical approach was employed. Early in the process a review of literature and prior investigations was undertaken to identify gaps in information. The resolution of identified gaps required geochemical investigations for acid base chemistry and multi-elements, surveys of density of deposited tailings, compaction reduction studies through ripping trials with different dozers, ripper depth and configurations, geotechnical assessment of the existing walls, and an extensive upper surface closure option review, followed by a field trial to determine optimum cover designs for rehabilitation and closure. Planning for tailings closure can often be a two to three year process, or longer for more problematic tailings stored in complex facilities, or facilities located on mine sites that have competing resource requirements. At the time of writing this paper, the closure earthworks for the Three Cell TSF were in the final stages, resulting in an active closure process of five years duration. It is expected that by late 2009 all earthworks will be complete and an “as-built decommissioning report” will be prepared. The site will then move into the monitoring phase. The closure of the TSF has not been without challenges and included a one in 910 year annual exceedance probability (AEP) rainfall event which produced large-scale surface water flow and erosion. Other challenges included drought conditions, cold winters, extreme summer temperatures and perceived edaphic difficulties. This paper presents the process employed for the closure of the Three Cell TSF, the investigations, the issues encountered and the final closure strategy.